خروج عن المذھب اور عصر حاضر کے تقاضے : فقہ حنفی کے تناظر میں - ناصر الدین; محمد ابراہیم (jihat-ul-islam, 2019)
In the light of Quran, there are two types of people. One type is the people of knowledge and the other type is populace. The populace always takes guidance from the people with knowledge. When Islamic teachings were compiled, Islamic jurisprudence remained confined to only four jurisprudences; the Hanafi, the Malaki, Shafee, Hanbali, and the rest of the Jurisprudences ceased to exist. These four jurisprudences are basically different aspect of Islamic Shariat. All these four jurisprudence are true but to prevent people from following different jurisprudences as per their whims and whishes one particular jurisprudence is asked to be followed.In addition to that the people of knowledge have always decreed in association with another jurisprudences. Whenever a problem was confronted then the solution was sought from the other jurisprudence as well. Such an approach is called decreeing on other jurisprudences. However, such an approach has certain conditions. In our Hanafi jurisprudence, we have certain problems which need adopting such an approach. This research details out the conditions of giving a decree on other jurisprudences, in the light of the problems being face by Hanafi school of thought for which decreeing on schools have become mandatory.